Annie Leibovitz - Frayn, Rebecca; Eley, Mike (Weekend Television, 1993)
This documentary takes a look at Leibovitz's work from her beginnings as a Rolling Stone Magazine contributor in the 1970s (which left her with a serious drug addiction), through her reemergence in the 1980s as Vanity Fair's chief photographer. Through interview footage with some of the people she has worked with, including her former editor at Rolling Stone, Jann Wenner, along with Mick Jagger and Hunter S. Thompson, the story of how she became who she is unfolds. Leibovitz also shares insight into her work and development as an artist, recounting some of the circumstances surrounding her most famous images, including the last portrait of John Lennon taken the day before his assassination. Home movies with her family tell the story of her childhood and her interest in the camera, taking us to the retrospective exhibition that would tour the world with the iconic images she has captured during her career ... [www.digitallyobsessed.com]